Depression and meaning of life in junior high school-going adolescents: A descriptive study - Aprilia, Andini Rosa; Agustina, Habsyah Saparidah; Fauziah, Wardah (Program Studi Keperawatan, Politeknik Negeri Subang, 2023)
Background: Depression is one of the mental health disorders that has increased very significantly every year. As many as 280,000,000 people experience depression worldwide. Depression can occur in adolescents who are characterized by having a less meaningful life.. Purpose: To determine the picture of Depression and the meaning of life in junior high school-going adolescents. Methods: A descriptive study using a cross-sectional approach was conducted at SMPN (Junior High School) 1 Kalijati in Subang City, with a population of 78, 9th grade students, and used cluster random sampling. This study used two measuring instruments, namely the Scale of Life Meaningfulness, consisting of 36 items, and the Beck Depression Inventory-II version of Indonesian, consisting of 21 items. The data are presented as a frequency distribution and percentage. Results: The level of meaningfulness of life is nearly half in the moderate and high categories, respectively, for as many as 24 respondents (30.77%). Almost half of the adolescents (49%) had mild symptoms of depression. Conclusion: The findings contribute to knowledge about the meaningfulness of life in adolescents and depression in adolescents. Junior high school-going adolescents have peer pressure, academic expectations, and body changes. This factor may potentially influence adolescent psychological health and requires future research.